Experience of implementing the basic principles of the bologna process in the training of specialists in clinical laboratory diagnostics - Sitalo, Serhiy (ScienceRise. Pedagogical education (Online), 2025)
The education system in any country is an important link in public life. Ukraine, as an independent state, has long been on a course for European integration. However, its entry into the scientific and educational international space forces it to modernize the education system in the light of modern requirements. This is a necessary condition for fully joining the Bologna process. The implementation of the medical education system in modern conditions, the possibilities for its reform, the problems, caused by the need to improve the quality of training of graduates of medical institutions of higher education, persistently require new effective approaches to setting up and organizing the educational process. Undoubtedly, the rapid progress of medical and pedagogical science necessitates the search and implementation of new effective technologies in the system of obtaining knowledge. The introduction of innovative technologies with elements of interactivity can ensure the proper training of a specialist doctor in accordance with existing medical standards. The use of modern technologies based on the Bologna process in the educational process when training specialists in clinical laboratory diagnostics creates new opportunities for implementing the didactic principles of individualization and differentiation of learning, has a positive effect on the development of cognitive activity of students, their creative activity, the level of consciousness, and implements the conditions for the transition from training to self-education. The effectiveness of the use of pedagogical technologies in the educational process has been confirmed by research works by many authors. Today, a comprehensive theoretical development of the problem of using modern pedagogical technologies in the professional training of a specialist in postgraduate education is gaining particular urgency and significance. Modern technologies in education are considered as a means, by which a new educational paradigm of the formation of the integrity of the educational process can be implemented. The use of modern innovative technologies is one of the most promising areas of development of higher education, which contribute to greater individualization of the educational process, intensification of training, formation and self-actualization of the personality of specialists in clinical laboratory diagnostics. The technology of developing critical thinking is the foundation for mastering new types of professional activity. The subject of any innovative technology is the specific interactions of students and teachers in various types of activity, organized on the basis of precise systematization, algorithmization, structuring and standardization of methods and techniques of teaching with the use of technical means. Thus, the implementation of modern technologies contributes to the fact that in the student's activity there is a transformation of the transition from learning as a function of memorization-reproduction to learning as an intensive intellectual activity Система освіти у будь-якій країні – важлива ланка суспільного життя. Україна, як незалежна держава, уже давно взяла курс на євроінтеграцію. Однак її входження у науковий і освітній міжнародний простір змушує здійснювати модернізацію системи освіти у світлі сучасних вимог. Це є необхідною умовою, щоб повноцінно долучитися до Болонського процесу. Реалізація системи медичної освіти в сучасних умовах, можливості щодо її реформування, проблеми, зумовлені потребою у підвищенні якості підготовки випускників медичних закладів вищої освіти, наполегливо вимагають нових ефективних підходів до налаштування та організації освітнього процесу. Безперечно, стрімкий прогрес медичної та педагогічної науки зумовлює пошук і впровадження нових ефективних технологій у систему отримання знань. Запровадження інноваційних технологій з елементами інтерактивності здатне забезпечити належну підготовку лікаря-спеціаліста відповідно до існуючих медичних стандартів. Використання сучасних технологій на основі Болонського процесу у навчальному процесі при підготовці фахівців з клінічної лабораторної діагностики створює нові можливості реалізації дидактичних принципів індивідуалізації та диференціації навчання, позитивно впливає на розвиток пізнавальної діяльності слухачів, їх творчої активності, рівень свідомості, реалізує умови переходу від навчання до самоосвіти. Ефективність використання педагогічних технологій у навчальному процесі підтверджена дослідницькими роботами багатьох авторів. На сьогоднішній день всеосяжна теоретична розробка проблеми використання сучасних педагогічних технологій у професійній підготовці спеціаліста в умовах післядипломної освіти набуває особливої гостроти та значимості. Сучасні технології в освіті розглядаються як засіб, з допомогою якого може бути реалізована нова освітня парадигма становлення цілісності навчального процесу. Використання сучасних інноваційних технологій – один із найперспективніших напрямів розвитку вищої освіти, які сприяють більшій індивідуалізації навчального процесу, інтенсифікації навчання, формуванню та самоактуалізації особистості фахівців з клінічної лабораторної діагностики. Технологія розвитку критичного мислення є фундаментом для засвоєння нових видів професійної діяльності. Предметом будь-якої інноваційної технології є конкретні взаємодії слухачів та викладачів у різноманітних видах діяльності, організовані на базі точної систематизації, алгоритмізації, структурування та стандартизації способів та прийомів навчання із застосуванням технічних засобів. Таким чином, втілення сучасних технологій сприяє тому, що в діяльності слухача відбувається трансформація переходу від навчання, як функції запам’ятовування-відтворювання, до навчання – як інтенсивної інтелектуальної діяльності